The effect of adding dexamethasone to adductor block and IPACK block on acute postoperative, rebound, and chronic pain following knee arthroplasty—1-year follow-up - Sreckovic, Svetlana; Milovanovic, Darko; Vukman, Petar; Djukanovic, Marija; Simic, Marko; Vesic, Jovan; Milenkovic, Marija; Aleksic, Milica; Ladjevic, Nebojsa (Frontiers in Medicine, 2025)
The analgesic efficacy of nerve blocks depends on the duration of local anesthetics, whose effects can be extended with adjuvant drugs. This prospective interventional study aimed to assess the impact of adding dexamethasone to levobupivacaine on the postoperative analgesic efficacy of the adductor canal block (ACB) and IPACK block after knee arthroplasty (TKA), as well as the incidence of rebound and chronic postsurgical pain. One year after TKA, 80 patients were analyzed (dexamethasone vs. control group). Opioid analgesics were administered to 10% of patients in the dexamethasone group and 50% of patients in the control group (χ2 = 13.393, p < 0.001), with no difference in opioid dosage (p = 0.368) during the first 24 h postoperatively. Rebound pain was observed in 5% of patients in the dexamethasone group and 30% in the control group (χ2 = 7.013, p = 0.008). Chronic postsurgical pain 1 year after TKA was found in 5% of patients in the control group, without significant differences between the groups. Adding dexamethasone to the local anesthetic for ACB and IPACK blocks, along with a non-opioid scheduling strategy, enhances postoperative pain management, reduces opioid consumption, and helps decrease the occurrence of rebound pain and chronic postsurgical pain 1 year after TKA.